Study on Agronomic and Economic Performance Characteristics of Cassava (Manihot utillisima L.) in Gunungkidul Regency Special Region of Yogyakarta - Gatot Supangkat Samidjo; Sarjiyah Sarjiyah; Haryono Haryono; Reynaldi Gustami (Universitas Muhammadiyah Yogyakarta, 2018)
Study on agronomic and economic performance characteristics of cassava (Manihot utillisima L.) in Gunungkidul Regency Special Region of Yogyakarta was conducted in April – August 2016. The research aimed to identify the agronomic and economic performance characteristics of cassava in Gunungkidul regency. Technical implementation of the survey method was conducted by observation and interview. The location of research sampling was determined by stratified random sampling method based on the category of district that has the most or broadest, medium, and small amount of cassava planting area. The respondents were chosen by purposive sampling method as much as 10% from the number of cassava farmers in a village or farmer group. The data were analyzed by descriptive and farming system analysis. The research result showed that there were some cassava cultivars observed, i.e. ‘Ketan’, ‘Pahit’, ‘Adira’, ‘Ireng’, ‘GatotKaca’, ‘Genjah’, ‘Mentega’, ‘Oyeng’, ‘Randu’, ‘Ambira’, ‘Klentheng’, ‘Srondol’, ‘PandesiHijau’, ‘Adira 1’, ‘Pandesi’, ‘Kirik’, ‘Gambyong’, ‘Jowo’, ‘Bamban’, ‘Kacibali’, ‘UJ-5’, ‘Marekan’, ‘Kresno’, ‘Meni’, ‘Merah’, ‘Malang’, ‘Kropak’ and ‘Aban’. Cultivation technology of cassava applied in Gunungkidul Regency is conventional technology. The maximum tillage system is applied in the soil tillage. Generally, Cassava is grown intercropping with rice, beans and maize. Manure is applied in cultivation technology and weeding is done six until ten times. There are eight types of pests attacking cassava plants. Cassava is harvested in seventh until tenth month after planting. Cassava farming is feasible in Gunungkidul Regency with R/C ratio (Revenue Cost Ratio) and B/C ratio (Benefit Cost Ratio) gained 1.